Child population, economic development and regional inequality of education resources in China. (March 2020) - Peng, Huamin; Qi, Lin; Wan, Guowei; Li, Bingqin; Hu, Bo
Highlights: Despite legislation and financial redistribution, unequal access to educational resources in China remains. The government has failed to provide sufficient financial support to underdeveloped provinces. In underdeveloped areas, financial capacity is lower, but educational need is higher. Abstract: There is great inequality of educational resources between different provinces in China due to unbalanced economic development. Despite continued redistribution of financial resources by the central government in favor of poorer provinces, educational inequality remains. In this paper, we argue that focusing on educational resources is far from sufficient. Poorer provinces do not only suffer from a lower level of educational resources, but they also have more children to educate, i.e. a greater need for education. Combining and analyzing the data in the Sixth National Population Census of China and the official statistics on education spending and resources, we found that provincial-level variations in the child population and the child dependency ratio have made access to educational resources even more unequal given the unequal financial capacity at the provincial level. Poorer provinces face a higher child dependency ratio and have lower economic development, and these two factors jointly lead to limited educational resources. Apart from a much higher level of redistribution in favor of less developed provinces, encouraging more balanced distribution of teachers and more broadly promoting economic equality are essential to reduce inequality in educational resources in China.